(untitled) (American Journal of Islam and Society, 2012)
This exhaustive series of fifteen essays, all produced by the author during 1989-2005, covers many relevant facets of the Mamluk slave dynasty (1250– 1517). By collecting these previously published essays in a single volume, a trajectory of interpretation can be contextualized and understood. Nasser Rabbat, a key figure in the contemporary study of Islamic architecture, is director of the Aga Khan Program for Islamic Architecture at MIT. The essays, organized into four thematic parts, begin with a conceptual understanding of the Mamluks and their role and then look at their architecture through the lenses of history, language, and cultural index ...